Kategoryzacja projektów w controllingu portfeli projektów - Kozarkiewicz, Alina (Categorizing of projects in project portfolio controlling, 2008)
The aim of this paper is to present selected issues of project portfolio controlling. The matters discussed in this article are related mostly to the categorization of projects at various stages of portfolio creation. In the first part of the article, the basic definitions concerning project portfolio and project portfolio controlling are presented. In the next parts, the major issues and tools of categorization are presented. They are demonstrated in relation to the three main stages: the stage of projects' identification, the stage of projects' selection, and finally to the stage when the strategic balance of portfolio is to be assured.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 222-230